Bypass, Loss, and Heat Transfer in Aircraft Surface Coolers - Liu, Jason; Peck, James; Yazawa, Kazuaki; Fisher, Timothy S.; Shih, Tom I-P. (Frontiers in Mechanical Engineering, 2019)
Surface coolers are heat exchangers with fins on the air side. When air approaches the fins, a portion is diverted away (bypass) because of the adverse pressure gradients induced by the fins. Also, for the air that does flow between the fins, a portion exits (loss) because of pressure rise along the fins due to friction Both bypass and loss reduce the effectiveness of surface coolers to transfer heat to the air. In this study, steady RANS with the SST model (with and without conjugate heat transfer) were performed to examine how geometric and operating parameters affect bypass, loss, pressure drop, and heat transfer in two surface coolers commonly used in aircraft applications. Of the surface coolers, one has continuous fins, and the other has staggered or non-staggered segmented fins. Geometric parameter examined include: spacing between the fins (S/H = 0.2,0.4,0.6,0.8), thickness of the fins (t/H = 0.1, 0.2, 0.4), length of the fins (L/H = 1, 5, 10), and the height of the channel, where the surface cooler is placed (C/H = 2.5, 5, 10, 20, 40 cm), where H is the height of the fin, and C is the half the height of the channel. Operating parameters examined include: velocity (Vin = 32.5, 65, 97.5, and 135 m/s) and temperature (Tin = 300 and 473 K) of flow approaching the surface cooler, the fins’ wall temperature (Tw = 300, 320, 350, 375, 400, 493 K). Results obtained show C/H to significantly affect bypass and loss until C/H reaches about 20. Bypass, loss, and pressure drop all increase monotonically as the blockage created by the fins, t/(S+t), increases. The ratio of the Nusselt number to the pressure coefficient is a maximum when t/(S+t) = 0.33 for the conjugate cases and 0.5 for the isothermal cases. Vin, Tin and Tw were found to have negligible effects on bypass, but have appreciable effects on loss when spacing between the fins is small. For the geometries studied, segmenting the fins was found to increase loss, resulting in the worst heat-transfer rate and highest pressure drop.